A cholesteric liquid crystal microcapsule and preparation method thereof

By constructing a bilayer structure of liquid crystal microcapsules, the reaction of thiol compounds and epoxy compounds is used to form a stable shell layer, and the liquid crystal phase with opposite rotation directions is set, the problem of low reflectivity and fluidity of cholesteric phase is solved, and the application of high reflectivity and stability is achieved, which is suitable for the application of flexible devices.

CN119040007BActive Publication Date: 2025-03-07NALINWAY NANO TECHNOLOGY (SHANGHAI) CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411232608.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-04
Publication Date
2025-03-07
Estimated Expiration
2044-09-04

AI Technical Summary

Technical Problem

The existing cholesteric liquid crystals have low reflectivity in a single rotation direction. The two rotation directions lose their selective reflection characteristics due to racemic phenomena, and the fluidity makes it difficult to apply in flexible devices.

Method used

By constructing a bilayer structure of liquid crystal microcapsules, a stable shell layer is formed by reacting thiol compounds and epoxy compounds, and liquid crystals in opposite directions are arranged between the inner and outer shell layers to avoid contact with each other, prevent racemic phenomena, and introduce high refractive index sulfur atoms to improve reflectivity.

Benefits of technology

It realizes the high reflectivity and stability of liquid crystal microcapsules, avoids the occurrence of racemic phenomena, is suitable for the application of flexible devices, and improves the heat resistance and mechanical properties of microcapsules.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present invention relates to the technical field of liquid crystal materials, specifically to a cholesteric liquid crystal microcapsule and a preparation method thereof, comprising the following processes: mixing an emulsifier and deionized water to form an aqueous phase; taking a left-handed or right-handed liquid crystal, mixing and dispersing it with an epoxy compound to form an oil phase A; mixing the aqueous phase and the oil phase, shearing and emulsifying to obtain an emulsion A; adding a thiol compound and a catalyst to react to obtain an inner layer microcapsule; mixing a liquid crystal of another rotation direction, an inner layer microcapsule and an epoxy compound to form an oil phase B; mixing the oil phase B and the aqueous phase, shearing and emulsifying to obtain an emulsion B; adding a thiol compound and a catalyst to react to obtain a liquid crystal microcapsule. The present invention constructs a double-layer microcapsule by using an epoxy compound and a thiol compound, and respectively arranges two liquid crystal phases of opposite rotation directions in the inner shell layer and between the inner and outer shell layers to avoid mutual contact between the two, thereby preventing racemization and effectively improving the reflectivity of the prepared microcapsule.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of liquid crystal materials, in particular to a cholesteric liquid crystal microcapsule and a preparation method thereof. Background Art

[0002] Liquid crystal is a form of matter independent of the three states of gas, liquid and solid. It is an intermediate aggregation state between static solid and amorphous liquid. It has both the fluidity of liquid and the anisotropy of crystal. The arrangement of molecules has long-range order and short-range disorder. The arrangement state of liquid crystal molecules can be divided into nematic, cholesteric and smectic according to their symmetry. Cholesteric liquid crystal was first observed in the liquid crystal of cholesterol esters and halides, hence the name; its molecules are arranged in parallel in the plane and arranged in a spiral structure along the normal. This determines its special optical properties - selective reflection of wavelengths and circular dichroism. When it is used, cholesteric liquid crystal with a single rotation direction can only reflect circularly polarized light with the same rotation direction, and transmit the opposite direction, resulting in low reflection; the reflectivity of liquid crystal after microencapsulation is even lower. If the liquid crystals of two rotation directions are directly mixed, the left and right rotations will cancel each other out, and a "racemization" effect will occur to form a nematic liquid crystal, which no longer has the characteristics of selective emission. Moreover, cholesteric liquid crystal has a certain fluidity. When it is bent or squeezed, it will be distorted and cannot be used in flexible devices. Therefore, we propose a cholesteric liquid crystal microcapsule and a preparation method thereof. Summary of the invention

[0003] The object of the present invention is to provide a cholesteric liquid crystal microcapsule and a preparation method thereof to solve the problems raised in the above background technology.

[0004] In order to solve the above technical problems, the present invention provides the following technical solution: a method for preparing cholesteric liquid crystal microcapsules, comprising the following processes:

[0005] Step 1. Mix an emulsifier and deionized water to form an aqueous phase; take a left-handed or right-handed liquid crystal, mix and disperse it with an epoxy compound to form an oil phase A; mix the aqueous phase and the oil phase, shear and emulsify, and obtain an emulsion A;

[0006] Adding mercapto compounds and catalysts for reaction, washing, and centrifuging to obtain inner-layer microcapsules;

[0007] Step 2. Mixing the liquid crystal of another rotation direction, the inner layer microcapsules and the epoxy compound to form an oil phase B;

[0008] The oil phase B and the water phase are mixed and emulsified by shearing to obtain emulsion B;

[0009] Add mercapto compounds and catalysts for reaction; wash and centrifuge to obtain liquid crystal microcapsules.

[0010] Furthermore, the liquid crystal microcapsule includes the following structures from the inside to the outside: an inner liquid crystal phase, an inner shell layer, an outer liquid crystal phase and an outer shell layer;

[0011] The inner liquid crystal phase has an opposite rotation direction to the outer liquid crystal phase.

[0012] In the above technical scheme, by constructing a double shell layer of the liquid crystal microcapsule and setting liquid crystals of opposite rotation directions between the inner shell layer and the inner shell layer and the outer shell layer, a left-handed and right-handed liquid crystal layered structure is formed in the microcapsule structure, which can avoid the mutual cancellation between the left and right rotations and make it have a total reflection effect, so as to improve the reflectivity of the liquid crystal microcapsule.

[0013] Further, in the aqueous phase, the concentration of the emulsifier is 0.16 to 0.20 wt %;

[0014] The catalyst is 1,8-diazabicyclo[5.4.0]undec-7-ene (DBU);

[0015] The epoxy compound is one of ethylene glycol diglycidyl ether, trimethylolpropane triglycidyl ether, N,N,N',N'-tetraepoxypropyl-4,4'-diaminodiphenylmethane, E-20, E-44, E-51, and E-52;

[0016] The mercapto compound is one of phthalic acid dimethyl mercaptan, trimethylolpropane tris(3-mercaptopropionate), pentaerythritol tetrakis(3-mercaptopropionate), pentaerythritol tetrakismercaptoacetate, and inositol hexa(mercaptopropionate);

[0017] The process conditions of shear emulsification are: shear speed of 8000-12000 r / min, and shear time of 100-150 s.

[0018] Furthermore, the process conditions of the reaction are: reaction temperature is 25±5°C, reaction time is 8 to 12h;

[0019] After the reaction, alcohol washing, water washing, centrifugation-redispersion were performed three times in sequence to remove the dispersant and unreacted reactants.

[0020] Furthermore, in step 1, the mass ratio of the water phase to the oil phase A is 100:(4-5);

[0021] In the oil phase A, the mass ratio of liquid crystal to epoxy compound is (1-5): (0.8-1.0);

[0022] The amount of the mercapto compound is 0.9 to 1.2% of the epoxy compound, added in the form of an aqueous solution;

[0023] The amount of DBU catalyst used is 0.04-0.09wt% of the epoxy compound.

[0024] Furthermore, in step 2, the mass ratio of the water phase to the oil phase B is 100:(8-10);

[0025] In the oil phase B, the mass ratio of liquid crystal, inner layer microcapsule and epoxy resin is (0.8-2.2): (1.5-2.6): (0.8-1.0);

[0026] The amount of the mercapto compound is 1.0-1.5% of the epoxy compound, added in the form of an aqueous solution;

[0027] The dosage of catalyst DBU is 0.05-0.10wt% of the epoxy resin.

[0028] In the above technical scheme, liquid crystal is mixed with epoxy compound as oil phase (A), mixed with water phase, and an emulsion with fine particles is formed under the action of emulsifier and shear. Then, thiol compound is added, and under the action of catalyst, hydrogen atoms on thiol are captured to form sulfur anions with strong nucleophilic ability; sulfur anions react with epoxy groups according to SN2 mechanism, attack carbon atoms with less steric hindrance, perform proton transfer, and form thioether structure. Through the above mechanism, the epoxy compound can contact and solidify with the thiol compound at the oil-water interface by emulsion interfacial polymerization, and gradually form a stable core-shell structure, which is recorded as the inner shell layer. The inner layer microcapsule obtained is mixed with epoxy compound as oil phase B, emulsified again, and solidified by thiol compound to form an outer shell layer; liquid crystal is mixed in oil phase B so that it is between the inner shell layer and the outer shell layer after solidification, so as to obtain liquid crystal microcapsules. The cured product of epoxy compounds is used as the shell layer, and the reaction is carried out at room temperature. No energy input such as heating and ultraviolet radiation is required, and it has better processability. The prepared shell layer has good density and heat resistance, stability, and mechanical properties, and can be compatible with thermochromic liquid crystals to maintain its good performance.

[0029] By curing the epoxy compound with the mercapto compound, sulfur atoms with small dispersion and high molar refractive index are introduced into the shell structure. Compared with the ordinary light refractive index of the liquid crystal phase described in this application, the prepared inner and outer shell layers have a higher refractive index, which helps the liquid crystal microcapsule to obtain better reflectivity and reflection bandwidth.

[0030] Shear emulsification causes the liquid crystal to tend to change in order. As the frequency increases, the orientation of the lamellar liquid crystal phase changes from perpendicular to the flow direction to parallel to the flow direction; the particle size of the microcapsule decreases, and the liquid crystal phase can be anchored in the microcapsule, making its orientation more stable, which helps the prepared liquid crystal microcapsules to obtain higher reflectivity.

[0031] Further, the emulsifier is prepared by the following process:

[0032] Mix cholesterol and maleic anhydride in cyclohexane, heat to 82-88°C, stir and reflux for 150-200 minutes; cool, filter, recrystallize, and dry in vacuum at room temperature to obtain an esterification product;

[0033] The esterification product obtained in the previous step, epoxy resin, and ethylene glycol butyl ether are mixed, stirred, and heated to 105-115° C., N-methyldiethanolamine is slowly added over 30 minutes, and the mixture is kept warm for 3-5 hours under reflux reaction; vacuum distillation, washing, and drying are performed to obtain an epoxy ester compound;

[0034] The epoxy ester compound, sodium bisulfite and alcohol aqueous solution obtained in the previous step are mixed, stirred and heated to 95-100° C., and refluxed for 5-12 hours; filtered, acidified, washed and dried to obtain an emulsifier.

[0035] Further, the molar ratio of cholesterol to maleic anhydride is 1:(1.0-1.1);

[0036] The ratio of cholesterol to cyclohexane is (15-20) g / 100 mL.

[0037] Further, the epoxy resin is one of E-44 and E-51;

[0038] The mass ratio of esterification product to epoxy resin is 1:(1.0-1.5);

[0039] The amount of N-methyldiethanolamine used is 0.1-0.2% of the mass of the epoxy resin, and is added in the form of 0.5-1.0wt% N-methyldiethanolamine / ethylene glycol butyl ether solution;

[0040] The mass ratio of ethylene glycol butyl ether to epoxy resin is 1:(3-6).

[0041] Further, the mass ratio of the epoxy ester compound to sodium bisulfite is 10:(4.5-5.2);

[0042] The ratio of epoxy ester compound to alcohol aqueous solution is (5-15) g / 100 mL;

[0043] The alcohol aqueous solution is ethanol / water solution with a concentration of 80-90v;

[0044] Sodium bisulfite is added in the form of an aqueous solution, and the concentration of the sodium bisulfite solution is 5wt%.

[0045] In the above technical scheme, cholesterol and maleic anhydride undergo esterification reaction to generate cholesterol maleic acid ester containing carboxyl and double bonds, which is recorded as esterification product. The esterification product and epoxy resin are mixed, and an epoxy ester structure is generated through the reaction between carboxyl and epoxy groups, which is recorded as epoxy ester compound. The epoxy ester compound is sulfonated with sodium bisulfite to make it amphiphilic, thereby generating an emulsifier (anionic surfactant) for liquid crystal microcapsules. The hydrophobic end in its molecular structure has a high similarity with the inner liquid crystal phase, and both are cholesterol ester derivatives, so that the two have good affinity and compatibility; and contain epoxy resin units, so that the prepared emulsifier can be well dissolved in the oil phase. The hydroxyl group and sulfonic acid group obtained by sulfonation in the epoxy ester structure are used as hydrophilic ends, which have good hydrophilic properties, so that the prepared emulsifier has good dispersibility in the aqueous phase; thereby achieving effective emulsification of the epoxy and cholesterol ester system, and the prepared product has good emulsification properties.

[0046] Furthermore, the left-handed liquid crystal is a cholesteric phase liquid crystal, and is selected from a mixture of two or more of cholesterol acetate, cholesterol propionate, cholesterol n-butyrate, cholesterol nonanoate, cholesterol oleate, cholesteryl linoleate, cholesterol benzoate, cholesterol cinnamate, cholesterol ethyl carbonate, cholesterol oleyl carbonate, cholesteryl isostearyl carbonate, cholesteryl butyrate, cholesteryl carbonate, and cholesterol chloride.

[0047] Furthermore, the left-handed liquid crystal is a mixture of cholesterol nonanoate, cholesterol oleyl carbonate and cholesterol chloride, with a mass ratio of 50:45:5.

[0048] Furthermore, the left-handed liquid crystal is cholesterol acetate, cholesterol benzoate, cholesterol chloride, cholesterol nonanoate, and cholesterol oleyl carbonate, and the mass ratio is 1:2:3:2:1.

[0049] Furthermore, in step 1, after the reaction, the inner layer microcapsules are subjected to oxidation treatment, and the specific process is as follows:

[0050] The inner layer microcapsules, oxidant and ethanol are mixed, stirred and reacted at a temperature of 0 to 55° C. for 3 to 12 hours; the mixture is washed with alcohol, washed with water, centrifuged and redispersed for 3 cycles, and dried.

[0051] Further, the oxidant is one of hydrogen peroxide, peracetic acid, sodium periodate, and m-chloroperbenzoic acid;

[0052] When hydrogen peroxide is used as an oxidant, a catalyst needs to be added.

[0053] Further, the mass ratio of the inner layer microcapsules and the oxidant is 1:(1-4);

[0054] The ratio of the inner layer microcapsules to ethanol is (1-2) g / 100 mL.

[0055] Furthermore, the right-handed liquid crystal is a doping of nematic liquid crystal and a right-handed chiral agent.

[0056] The nematic phase liquid crystal is a mixture of one or more of 4-ethylbiphenylnitrile, 4'-n-butyl-4-cyanobiphenyl, 4-propyl-4'-cyanobiphenyl, 4-cyano-4'-pentylbiphenyl, 4-heptyl-4'-cyanobiphenyl, trans-4'-(4-pentylcyclohexyl)-[1,1'-biphenyl]-4-nitrile, and E7;

[0057] The right-handed chiral reagent is one or more of R1011, R5011, R6N, R811, CB15 and ionic liquid.

[0058] In the above technical solution, an oxidant is used to oxidize the sulfide on the surface of the inner microcapsule into sulfoxide and sulfone groups, and to oxidize the unreacted mercapto groups into sulfonic acid groups, which can act as proton donors in hydrogen bonds and self-assemble with the nitrogen-containing liquid crystal phase through hydrogen bonds, so that the right-handed liquid crystal tends to aggregate and adsorb on the surface of the inner shell layer, which is more conducive to the coating of the liquid crystal phase by epoxy resin and its cured product, and is conducive to the increase of the liquid crystal phase loading. The orderly arrangement of the liquid crystal phase on the surface of the inner shell layer, with its director being more perpendicular to the direction of the light source, can effectively prevent the narrowing of the reflection band and avoid the blue shift phenomenon, thereby helping to improve the reflectivity of the liquid crystal microcapsule.

[0059] Furthermore, in step 1, after the oxidation treatment, the inner layer microcapsules are doped with silver nanoparticles, and the specific process is as follows:

[0060] The inner layer microcapsules are dispersed in deionized water, polyvinyl pyrrolidone is added, and stirred until it is dissolved; silver nitrate is added under light-proof conditions, and stirred for 20 to 30 minutes; ascorbic acid is added, and stirred for reaction for 120 to 180 minutes; centrifugation is performed, washing with water, and drying is performed to obtain the product.

[0061] Furthermore, the ratio of the inner layer microcapsules to deionized water is (4-5) mg / mL;

[0062] The mass ratio of the inner layer microcapsules, polyvinyl pyrrolidone, silver nitrate and ascorbic acid is 10: (1-4): (0.1-1.0): (0.4-3.5).

[0063] In the above technical solution, the silver ions in the silver nitrate are adsorbed by the sulfonyl group on the surface of the inner shell layer, and the silver ions are reduced by a reducing agent, thereby forming silver nanoparticles in the inner shell layer, and realizing a small amount of doping of silver nanoparticles between the inner and outer shell layers. When incident light is irradiated, the silver nanoparticles can couple and resonate with it, producing a certain degree of field enhancement effect, which can effectively improve the reflectivity of the microcapsule and enhance the intensity of reflected light.

[0064] Furthermore, in step 2, after the reaction, the liquid crystal microcapsules are subjected to oxidation treatment, and the specific process is as follows:

[0065] The liquid crystal microcapsules, oxidant and ethanol are mixed, stirred and reacted at a temperature of 0 to 55° C. for 3 to 12 hours; the mixture is washed with alcohol, washed with water, centrifuged and re-dispersed for 3 cycles, and dried.

[0066] Further, the oxidant is one of hydrogen peroxide, peracetic acid, sodium periodate, and m-chloroperbenzoic acid;

[0067] When hydrogen peroxide is used as an oxidant, a catalyst needs to be added.

[0068] Further, the mass ratio of the liquid crystal microcapsule to the oxidant is 1:(1-4);

[0069] The ratio of liquid crystal microcapsules to ethanol is (1-2) g / 100 mL.

[0070] In the above technical solution, an oxidant is used to react an epoxy compound with a mercapto compound, and the formed sulfide structure is oxidized and converted into an oxidized sulfone, so that the glass transition temperature of the shell layer is increased, the polarity and rigidity are higher, the resistance to thermal deformation is enhanced, and the prepared liquid crystal microcapsules have better strength and stability. If the outer shell layer is not oxidized, the polyhydroxy sulfide segment formed by the reaction of the epoxy compound and the mercapto compound is highly flexible, which is conducive to its application in flexible devices.

[0071] Compared with the prior art, the present invention has the following beneficial effects:

[0072] 1. A cholesteric liquid crystal microcapsule and a preparation method thereof of the present invention, a double-layer microcapsule is constructed by epoxy compounds and mercapto compounds, two liquid crystal phases of opposite rotation directions are respectively arranged in the inner shell layer and between the inner and outer shell layers to avoid mutual contact between the two, thus preventing racemization and effectively improving the reflectivity of the prepared microcapsule.

[0073] 2. A cholesteric liquid crystal microcapsule and a preparation method thereof of the present invention, wherein the microcapsule shell is constructed by a mercapto-cured product of an epoxy compound, and a sulfur atom with a high refractive index is introduced, thereby increasing the refractive index of the shell, and helping the microcapsule to obtain better reflectivity and reflection bandwidth. The shell is then oxidized to convert the generated thioether into a sulfone group with higher rigidity, further improving the heat resistance, stability and mechanical properties of the microcapsule shell, so that it can better adapt to the application environment of thermochromic liquid crystals; and can self-assemble with a nitrogen-containing liquid crystal phase through hydrogen bonds, so that right-handed liquid crystals tend to aggregate and adsorb on the inner shell surface, which is more conducive to the coating of the liquid crystal phase by epoxy resin and its cured product, and is beneficial to the increase of the liquid crystal phase loading.

[0074] 3. A cholesteric liquid crystal microcapsule and a preparation method thereof of the present invention, wherein an emulsifier is prepared by cholesterol, maleic anhydride, epoxy resin and sodium sulfite, and an amphiphilic compound having an epoxy resin and cholesterol structure is prepared by esterification and sulfonation reactions, which is applied to the emulsification system of the present application, thereby achieving effective emulsification of the epoxy and cholesteric systems, improving the emulsification performance, and promoting the refinement and stabilization of the emulsification system.

[0075] 4. A cholesteric liquid crystal microcapsule and a preparation method thereof of the present invention, through the sulfonyl group formed on the surface of the inner shell layer after oxidation, silver nanoparticles are doped using silver nitrate and a reducing agent. A small amount of silver nanoparticles doped between the inner and outer shell layers can couple with the incident light to resonate, produce a field enhancement effect to a certain extent, thereby improving the reflectivity of the microcapsule and enhancing the intensity of the reflected light. DETAILED DESCRIPTION

[0076] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0077] In the following specific implementations,

[0078] Left-handed liquid crystal: a mixture of cholesterol nonanoate, cholesterol oleyl carbonate, and cholesterol chloride in a mass ratio of 50:45:5;

[0079] The right-handed liquid crystal is obtained by mixing the nematic phase liquid crystal E7 and the right-handed chiral agent R811, heating and melting until the system is transparent, stirring for 2 hours, and cooling; the mass ratio of E7 to R5011 is 100:0.3;

[0080] The catalyst is 1,8-diazabicyclo[5.4.0]undec-7-ene (DBU);

[0081] N-methyldiethanolamine was added in the form of a 1.0 wt% N-methyldiethanolamine / ethylene glycol butyl ether solution;

[0082] Sodium bisulfite was added in the form of a 5 wt % aqueous solution;

[0083] The thiol compound is added in the form of an aqueous solution;

[0084] Epoxy resin: E-20, E-44, E-51, E-52, from Bluestar Chemical New Materials Co., Ltd.;

[0085] Polyethylene glycol: PEG10000, from Sinopharm Group; the following experiments are all small-scale laboratory tests and can be expanded in equal proportions.

[0086] Embodiment 1: A method for preparing cholesteric liquid crystal microcapsules, comprising the following process:

[0087] Step 1. Preparation of emulsifier:

[0088] 15 g of cholesterol and 3.9 g of maleic anhydride were mixed in 100 mL of cyclohexane, heated to 82°C, stirred and refluxed for 150 min; cooled, filtered, recrystallized, and dried under vacuum at room temperature to obtain an esterified product;

[0089] 10g of esterification product, 1.0g of epoxy resin E-20 and 0.3g of ethylene glycol butyl ether were mixed, stirred and heated to 105°C, 0.1% N-methyldiethanolamine (relative to epoxy resin) was slowly added over 30 minutes, and the mixture was kept at reflux for 5 hours; vacuum distillation, washing and drying were performed to obtain epoxy ester compound;

[0090] 10 g of epoxy ester compound, 4.5 g of sodium bisulfite, and 200 mL of 80 v% alcohol aqueous solution were mixed, stirred and heated to 95 °C, and refluxed for 8 h; filtered, acid precipitated, washed, and dried to obtain an emulsifier;

[0091] Step 2. Preparation of inner layer microcapsules:

[0092] The emulsifier and deionized water are mixed to form an aqueous phase, and the concentration of the emulsifier is 0.16wt%; the left-handed liquid crystal is taken and mixed and dispersed with the epoxy compound trimethylolpropane triglycidyl ether to form an oil phase A, and the mass ratio of the left-handed liquid crystal to the epoxy compound is 2:0.8; the aqueous phase and the oil phase are mixed, and the mass ratio of the aqueous phase to the oil phase A is 100:4; shear emulsification is performed at a shear rate of 8000r / min and a shear time of 100s to obtain emulsion A; 0.9% of the mercapto compound (relative to the epoxy compound) trimethylolpropane tris (3-mercaptopropionate) and 0.04wt% of the catalyst are added and reacted at 25°C for 8h; washing and centrifugation are performed to obtain inner layer microcapsules A;

[0093] 1 g of inner layer microcapsule A, 2 g of oxidant m-chloroperbenzoic acid, and 100 mL of ethanol were mixed, stirred and reacted at 5°C for 3 h; alcohol washing, water washing, centrifugation-redispersion were performed in sequence for 3 cycles, and dried to obtain inner layer microcapsule B;

[0094] Disperse 10g of inner layer microcapsule B in 2.0L of deionized water, add 1g of polyvinyl pyrrolidone, and stir until it is dissolved; slowly add 0.1g of silver nitrate within 30min under light-proof conditions, stir for 20min; slowly add 0.4g of ascorbic acid within 30min, stir and react for 120min; centrifuge, wash with water, and dry to obtain inner layer microcapsules, including inner layer liquid crystal phase and inner shell layer;

[0095] Step 3. Preparation of liquid crystal microcapsules:

[0096] The right-handed liquid crystal, inner microcapsules and epoxy compound E-20 are mixed to form oil phase B, wherein the mass ratio of liquid crystal, inner microcapsules and epoxy resin is 1.1:1.5:0.8; the oil phase B and the water phase are mixed, wherein the mass ratio of the water phase to the oil phase B is 100:8; emulsification is performed by shearing at a shear rate of 8000 r / min and a shear time of 100 s to obtain emulsion B; 1.0% of mercapto compound trimethylolpropane tris(3-mercaptopropionate) and 0.05 wt% of catalyst are added for reaction; washing and centrifugation are performed to obtain liquid crystal microcapsules A;

[0097] 1 g of liquid crystal microcapsule A, 2 g of oxidant m-chloroperbenzoic acid, and 100 mL of ethanol were mixed, and stirred for reaction at 5°C for 3 h; alcohol washing, water washing, centrifugation-redispersion were performed in sequence for 3 cycles, and dried to obtain liquid crystal microcapsules, including inner layer microcapsules, outer layer liquid crystal phase, and outer shell layer.

[0098] Embodiment 2: A method for preparing cholesteric liquid crystal microcapsules, comprising the following process:

[0099] Step 1. Preparation of emulsifier:

[0100] 18g of cholesterol and 4.8g of maleic anhydride were mixed in 100mL of cyclohexane, heated to 85°C, stirred and refluxed for 180min; cooled, filtered, recrystallized, and dried under vacuum at room temperature to obtain an esterification product;

[0101] 10g of esterification product, 1.2g of epoxy resin E-20 and 0.3g of ethylene glycol butyl ether were mixed, stirred and heated to 110°C, 0.2% of N-methyldiethanolamine (relative to epoxy resin) was slowly added over 30 minutes, and the mixture was kept at reflux for 4 hours; vacuum distillation, washing and drying were performed to obtain epoxy ester compound;

[0102] 10 g of epoxy ester compound, 4.8 g of sodium bisulfite, and 100 mL of 85% alcohol aqueous solution were mixed, stirred, heated to 98°C, and refluxed for 6 h; filtered, acid precipitated, washed, and dried to obtain an emulsifier;

[0103] Step 2. Preparation of inner layer microcapsules:

[0104] The emulsifier and deionized water are mixed to form an aqueous phase, and the concentration of the emulsifier is 0.18wt%; the left-handed liquid crystal is taken and mixed and dispersed with the epoxy compound N,N,N',N'-tetraepoxypropyl-4,4'-diaminodiphenylmethane to form an oil phase A, and the mass ratio of the left-handed liquid crystal to the epoxy compound is 3:0.9; the aqueous phase and the oil phase are mixed, and the mass ratio of the aqueous phase to the oil phase A is 100:4.5; shear emulsification is performed at a shear rate of 10000r / min and a shear time of 120s to obtain emulsion A; 1.0% of the thiol compound (relative to the epoxy compound) pentaerythritol tetrathioglycolate and 0.06wt% of the catalyst are added and reacted at 25°C for 10h; washing and centrifugation are performed to obtain inner layer microcapsules A;

[0105] 1.5 g of inner layer microcapsule A, 3 g of oxidant m-chloroperbenzoic acid, and 100 mL of ethanol were mixed, stirred and reacted at 2°C for 5 h; alcohol washing, water washing, centrifugation-redispersion were performed in sequence for 3 cycles, and dried to obtain inner layer microcapsule B;

[0106] Disperse 10g of inner layer microcapsule B in 2.2L of deionized water, add 2g of polyvinyl pyrrolidone, and stir until it is dissolved; slowly add 0.5g of silver nitrate within 30min under light-proof conditions, stir for 25min; slowly add 1.0g of ascorbic acid within 30min, stir and react for 150min; centrifuge, wash with water, and dry to obtain inner layer microcapsules, including inner layer liquid crystal phase and inner shell layer;

[0107] Step 3. Preparation of liquid crystal microcapsules:

[0108] The right-handed liquid crystal, inner layer microcapsules and epoxy compound E-20 are mixed to form oil phase B, wherein the mass ratio of liquid crystal, inner layer microcapsules and epoxy resin is 1.6:2.0:0.9; the oil phase B and the water phase are mixed, wherein the mass ratio of the water phase to the oil phase B is 100:9; emulsification is performed by shearing, the shear rate is 10000r / min, and the shear time is 120s to obtain emulsion B; 1.2% of mercapto compound pentaerythritol tetrathioglycolate and 0.08wt% of catalyst are added for reaction; washing and centrifugation are performed to obtain liquid crystal microcapsules A;

[0109] 1.5 g of liquid crystal microcapsule A, 3 g of oxidant m-chloroperbenzoic acid, and 100 mL of ethanol were mixed, stirred and reacted at 2°C for 5 h; alcohol washing, water washing, centrifugation-redispersion were performed in sequence for 3 cycles, and dried to obtain liquid crystal microcapsules, including inner microcapsules, outer liquid crystal phases, and outer shell layers.

[0110] Embodiment 3: A method for preparing cholesteric liquid crystal microcapsules, comprising the following process:

[0111] Step 1. Preparation of emulsifier:

[0112] Mix 20g cholesterol and 5.5g maleic anhydride in 100mL cyclohexane, heat to 88°C, stir and reflux for 200min; cool, filter, recrystallize, and dry in vacuum at room temperature to obtain an esterification product;

[0113] 10g of esterification product, 1.5g of epoxy resin E-20 and 0.3g of ethylene glycol butyl ether were mixed, stirred and heated to 115°C, 0.2% N-methyldiethanolamine (relative to epoxy resin) was slowly added over 30 minutes, and the mixture was kept at reflux for 3 hours; vacuum distillation, washing and drying were performed to obtain epoxy ester compound;

[0114] 10 g of epoxy ester compound, 5.2 g of sodium bisulfite, and 100 mL of 90% alcohol aqueous solution were mixed, stirred and heated to 100°C, and refluxed for 5 h; filtered, acid precipitated, washed, and dried to obtain an emulsifier;

[0115] Step 2. Preparation of inner layer microcapsules:

[0116] The emulsifier and deionized water are mixed to form an aqueous phase, and the concentration of the emulsifier is 0.20wt%; the left-handed liquid crystal is taken and mixed and dispersed with the epoxy compound N, N, N', N'-tetraepoxypropyl-4, 4'-diaminodiphenylmethane to form an oil phase A, and the mass ratio of the left-handed liquid crystal and the epoxy compound is 4:1; the aqueous phase and the oil phase are mixed, and the mass ratio of the aqueous phase to the oil phase A is 100:5; shear emulsification is performed at a shear rate of 12000r / min and a shear time of 150s to obtain an emulsion A; 1.2% of a thiol compound (relative to the epoxy compound) inositol hexa(mercaptopropionate) and 0.09wt% of a catalyst are added and reacted at 25°C for 12h; washing and centrifugation are performed to obtain an inner layer microcapsule A;

[0117] 2g of inner layer microcapsule A, 4g of oxidant m-chloroperbenzoic acid, and 100mL of ethanol were mixed, stirred and reacted at 0°C for 8h; alcohol washing, water washing, centrifugation-redispersion were performed in sequence for 3 cycles, and dried to obtain inner layer microcapsule B;

[0118] Disperse 10g of inner layer microcapsule B in 2.5L of deionized water, add 4g of polyvinyl pyrrolidone, and stir until it is dissolved; slowly add 1.0g of silver nitrate in 30 minutes under light-proof conditions, stir for 30 minutes; slowly add 3.5g of ascorbic acid in 30 minutes, stir and react for 180 minutes; centrifuge, wash with water, and dry to obtain inner layer microcapsules, including inner liquid crystal phase and inner shell layer;

[0119] Step 3. Preparation of liquid crystal microcapsules:

[0120] The right-handed liquid crystal, inner layer microcapsules and epoxy compound E-20 are mixed to form oil phase B, wherein the mass ratio of liquid crystal, inner layer microcapsules and epoxy resin is 2.1:2.6:1.0; the oil phase B and the water phase are mixed, wherein the mass ratio of the water phase to the oil phase B is 100:10; emulsification is performed by shearing at a shear rate of 12000 r / min and a shear time of 150 s to obtain emulsion B; 1.5% of thiol compound inositol hexamer (mercaptopropionate) and 0.10 wt% of catalyst are added for reaction; washing and centrifugation are performed to obtain liquid crystal microcapsules A;

[0121] 2 g of liquid crystal microcapsule A, 4 g of oxidant m-chloroperbenzoic acid, and 100 mL of ethanol were mixed, stirred and reacted at 0°C for 8 h; alcohol washing, water washing, centrifugation-redispersion were performed in sequence for 3 cycles, and dried to obtain liquid crystal microcapsules, including inner microcapsules, outer liquid crystal phases, and outer shell layers.

[0122] Comparative Example 1: A method for preparing cholesteric liquid crystal microcapsules, comprising the following processes:

[0123] Step 2. Preparation of inner layer microcapsules:

[0124] The emulsifier and deionized water are mixed to form an aqueous phase, and the concentration of the emulsifier is 0.16wt%; the left-handed liquid crystal is taken and mixed and dispersed with the epoxy compound trimethylolpropane triglycidyl ether to form an oil phase A, and the mass ratio of the left-handed liquid crystal to the epoxy compound is 2:0.8; the aqueous phase and the oil phase are mixed, and the mass ratio of the aqueous phase to the oil phase A is 100:4; shear emulsification is performed at a shear rate of 8000r / min and a shear time of 100s to obtain emulsion A; 0.9% of the mercapto compound (relative to the epoxy compound) trimethylolpropane tris (3-mercaptopropionate) and 0.04wt% of the catalyst are added and reacted at 25°C for 8h; washing and centrifugation are performed to obtain inner layer microcapsules A;

[0125] 1 g of inner layer microcapsule A, 2 g of oxidant m-chloroperbenzoic acid, and 100 mL of ethanol were mixed, stirred and reacted at 5°C for 3 h; alcohol washing, water washing, centrifugation-redispersion were performed in sequence for 3 cycles, and dried to obtain inner layer microcapsules, including an inner layer liquid crystal phase and an inner shell layer;

[0126] Step 1 and step 3 are the same as those in Example 1 to obtain liquid crystal microcapsules.

[0127] Comparative Example 2: A method for preparing cholesteric liquid crystal microcapsules, comprising the following processes:

[0128] Step 2. Preparation of inner layer microcapsules:

[0129] The emulsifier and deionized water are mixed to form an aqueous phase, and the concentration of the emulsifier is 0.16wt%; the left-handed liquid crystal is taken and mixed and dispersed with the epoxy compound trimethylolpropane triglycidyl ether to form an oil phase A, and the mass ratio of the left-handed liquid crystal to the epoxy compound is 2:0.8; the aqueous phase and the oil phase are mixed, and the mass ratio of the aqueous phase to the oil phase A is 100:4; shear emulsification is performed at a shear rate of 8000r / min and a shear time of 100s to obtain emulsion A; 0.9% of the mercapto compound (relative to the epoxy compound) trimethylolpropane tris (3-mercaptopropionate) and 0.04wt% of the catalyst are added and reacted at 25°C for 8h; washing and centrifugation are performed to obtain inner layer microcapsules, including an inner layer liquid crystal phase and an inner shell layer;

[0130] Step 1 and step 3 are the same as those in Example 1 to obtain liquid crystal microcapsules.

[0131] Comparative Example 3: A method for preparing cholesteric liquid crystal microcapsules, comprising the following processes:

[0132] Step 2. Preparation of inner layer microcapsules:

[0133] The emulsifier and deionized water are mixed to form an aqueous phase, and the concentration of the emulsifier is 0.16wt%; the left-handed liquid crystal is taken and mixed and dispersed with the epoxy compound trimethylolpropane triglycidyl ether to form an oil phase A, and the mass ratio of the left-handed liquid crystal to the epoxy compound is 2:0.8; the aqueous phase and the oil phase are mixed, and the mass ratio of the aqueous phase to the oil phase A is 100:4; shear emulsification is performed at a shear rate of 8000r / min and a shear time of 100s to obtain emulsion A; 0.9% of the mercapto compound (relative to the epoxy compound) trimethylolpropane tris (3-mercaptopropionate) and 0.04wt% of the catalyst are added and reacted at 25°C for 8h; washing and centrifugation are performed to obtain inner layer microcapsules, including an inner layer liquid crystal phase and an inner shell layer;

[0134] Step 3. Preparation of liquid crystal microcapsules:

[0135] The right-handed liquid crystal, inner microcapsules and epoxy compound E-20 are mixed to form an oil phase B, wherein the mass ratio of the liquid crystal, the inner microcapsules and the epoxy resin is 1:1.5:0.8; the oil phase B and the water phase are mixed, wherein the mass ratio of the water phase to the oil phase B is 100:8; shear emulsification is performed at a shear rate of 8000 r / min and a shear time of 100 s to obtain an emulsion B; 1.0% of the mercapto compound trimethylolpropane tris(3-mercaptopropionate) and 0.05 wt% of a catalyst are added for reaction; washing and centrifugation are performed to obtain a liquid crystal microcapsule, comprising an inner microcapsule, an outer liquid crystal phase and an outer shell layer;

[0136] Step 1 is the same as in Example 1 to obtain liquid crystal microcapsules.

[0137] Comparative Example 4: A method for preparing cholesteric liquid crystal microcapsules, comprising the following process:

[0138] Step 1. Preparation of emulsifier:

[0139] Cholesterol and epoxy resin E-20 were mixed, heated to 70°C under nitrogen atmosphere, 1% boron trifluoride-ether complex / anhydrous ether solution was added, and the mixture was reacted for 3 hours; the mixture was heated to 110°C and reacted in air atmosphere for 2 hours; the ether was removed by heating, and the mixture was cooled to obtain an emulsifier; the mass ratio of cholesterol to epoxy resin was 2:1;

[0140] Step 2 and step 3 are the same as those in Comparative Example 3 to obtain liquid crystal microcapsules.

[0141] Comparative Example 5: A method for preparing cholesteric liquid crystal microcapsules, comprising the following process:

[0142] 20 mL of 1 wt% gum arabic aqueous solution and 2 mL of 2 wt% OP-10 aqueous solution were mixed at 50°C, 1 g of left-handed liquid crystal was added, and the mixture was stirred at a speed of 2000 r / min for 20 min;

[0143] 20 mL of 2 wt % gelatin aqueous solution was added, and the pH of the system was adjusted to 4.5 with 10% acetic acid solution. The mixture was stirred at 50° C. and 400 r / min for 60 min. The mixture was cooled to room temperature, washed, and centrifuged to obtain liquid crystal microcapsules.

[0144] Experiment: Take the liquid crystal microcapsules obtained in Examples 1-3 and Comparative Examples 1-5 to prepare samples, test their properties respectively and record the test results:

[0145] Microcapsule performance: The particle size of the liquid crystal microcapsule sample was measured using a laser particle size analyzer, and the median particle size (median diameter) of the sample was recorded;

[0146] Record the initial weight W0 of the liquid crystal microcapsule, place the sample in dichloromethane and ultrasonically crush it for 60 min, filter it, collect the filtrate, evaporate it under reduced pressure to remove dichloromethane, record the mass Wc of the residual liquid, and calculate the ratio of Wc to W0 as the core material loading (%);

[0147] Reflection performance test: Use a fiber optic spectrometer to detect the reflectivity of the liquid crystal microcapsule sample;

[0148] Thermal stability test: A differential scanning calorimeter was used to detect the glass transition temperature (°C) of the microcapsule sample (shell layer). The experimental atmosphere was nitrogen and the heating rate was 10°C / min.

[0149]

[0150] According to the data in the above table, we can clearly draw the following conclusions:

[0151] The liquid crystal microcapsules obtained in Examples 1-3 are compared with the liquid crystal microcapsules obtained in Comparative Examples 1-5. The test results show that:

[0152] Compared with Comparative Examples 1-4, the liquid crystal microcapsules obtained in Examples 1-3 have higher liquid crystal loading, reflectivity and glass transition temperature data, and the particle size is relatively lower. This fully demonstrates that the present invention achieves an improvement in the reflectivity of the liquid crystal microcapsules, and a higher core material loading and thermal stability.

[0153] Compared with Example 1, the inner shell layer in Comparative Example 1 is not doped with silver nanoparticles; the inner shell layer in Comparative Example 2 is not oxidized and doped with silver nanoparticles; the inner and outer shell layers in Comparative Example 3 are not oxidized; compared with Comparative Example 3, the emulsifier in Comparative Example 4 is obtained by reacting cholesterol and epoxy resin; the liquid crystal microcapsules in Comparative Example 5 have different preparation processes and compositions. It can be seen from the data that the preparation process of the liquid crystal microcapsules and the settings of the components used in the present invention can improve their reflectivity, core material loading, and thermal stability.

[0154] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process method article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process method article or device.

[0155] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing cholesteric liquid crystal microcapsules, characterized in that: Including the following processes: Step 1. Mix an emulsifier and deionized water to form an aqueous phase; take a left-handed or right-handed liquid crystal, mix and disperse it with an epoxy compound to form an oil phase A; mix the aqueous phase and the oil phase, shear and emulsify, and obtain an emulsion A; Adding mercapto compounds and catalysts for reaction, washing, and centrifuging to obtain inner-layer microcapsules; Step 2. Mixing the liquid crystal of another rotation direction, the inner layer microcapsules and the epoxy compound to form an oil phase B; The oil phase B and the water phase are mixed and emulsified by shearing to obtain emulsion B; adding a thiol compound and a catalyst to react; washing and centrifuging to obtain liquid crystal microcapsules; In step 1, after the reaction, the inner layer microcapsules are subjected to oxidation treatment, and the specific process is: the inner layer microcapsules, the oxidant, and ethanol are mixed, and stirred at a temperature of 0 to 55° C. for 3 to 12 hours to obtain; In step 1, after oxidation treatment, the inner layer microcapsules are doped with silver nanoparticles. The specific process is as follows: The inner layer microcapsules are dispersed in deionized water, polyvinyl pyrrolidone is added, and stirred until it is dissolved; silver nitrate is added under light-proof conditions, and stirred for 20 to 30 minutes; ascorbic acid is added, and stirred for reaction for 120 to 180 minutes to obtain; Left-handed liquid crystal is cholesteric liquid crystal, and right-handed liquid crystal is a doping of nematic liquid crystal and right-handed chiral agent.

2. The method for preparing a cholesteric liquid crystal microcapsule according to claim 1, characterized in that: The emulsifier is prepared by the following process: Mix cholesterol and maleic anhydride in cyclohexane, heat to 82-88°C, stir and reflux for 150-200 minutes to obtain an esterification product; The esterification product obtained in the previous step, epoxy resin, and ethylene glycol butyl ether are mixed, stirred, and heated to 105-115° C., N-methyldiethanolamine is slowly added over 30 minutes, and the mixture is kept at reflux for 3-5 hours to obtain an epoxy ester compound; The epoxy ester compound, sodium bisulfite and alcohol aqueous solution obtained in the previous step are mixed, stirred and heated to 95-100° C., and refluxed for 5-12 hours to obtain an emulsifier.

3. The method for preparing cholesteric liquid crystal microcapsules according to claim 1, characterized in that: The epoxy compound is one of ethylene glycol diglycidyl ether, trimethylolpropane triglycidyl ether, N,N,N',N'-tetraepoxypropyl-4,4'-diaminodiphenylmethane, E-20, E-44, E-51, and E-52; The mercapto compound is one of phthalic acid dimethyl mercaptan, trimethylolpropane tris(3-mercaptopropionate), pentaerythritol tetrakis(3-mercaptopropionate), pentaerythritol tetrakismercaptoacetate, and inositol hexa(mercaptopropionate).

4. The method for preparing cholesteric liquid crystal microcapsules according to claim 1, characterized in that: The process conditions of the shear emulsification are: shear speed of 8000-12000 r / min, and shear time of 100-150 s.

5. The method for preparing cholesteric liquid crystal microcapsules according to claim 1, characterized in that: In step 2, after the reaction, the liquid crystal microcapsules are subjected to oxidation treatment, and the specific process is: the liquid crystal microcapsules, the oxidant, and ethanol are mixed, and the mixture is stirred and reacted at a temperature of 0 to 55° C. for 3 to 12 hours to obtain.

6. The method for preparing cholesteric liquid crystal microcapsules according to claim 1, characterized in that: In step 1, the mass ratio of the aqueous phase to the oil phase A is 100:(4-5); in the oil phase A, the mass ratio of the liquid crystal to the epoxy compound is (1-5):(0.8-1.0).

7. The method for preparing cholesteric liquid crystal microcapsules according to claim 1, characterized in that: In step 2, the mass ratio of the aqueous phase to the oil phase B is 100:(8-10); in the oil phase B, the mass ratio of the liquid crystal, the inner layer microcapsule, and the epoxy resin is (0.8-2.2):(1.5-2.6):(0.8-1.0).

8. A cholesteric liquid crystal microcapsule prepared by the preparation method according to any one of claims 1 to 7, characterized in that: The structure includes the following from the inside to the outside: an inner liquid crystal phase, an inner shell layer, an outer liquid crystal phase and an outer shell layer; the inner liquid crystal phase has an opposite rotation direction to the outer liquid crystal phase.

Citation Information

Patent Citations

  • Multi-thiol micro-capsule and its preparation method

    CN101116806A

  • Epoxy resin type polymer microsphere preparation method

    CN106939073A